FAIR VALUE AND COST APPROACHES IN ACCRETION ACCRETION OF SHEEP BIOLOGICAL ASSETS (CASE STUDY AT KENDAL OPEN PRIVATE FARM) - Setyowati, Ani; Permanasari, Rusdiana; Amalia, Naini Rizka; Soekaemi, Solichoel (STIE Pelita Nusantara Semarang, 2024)
The purpose of this study is to analyze and describe the measurement of the biological assets of sheep using the fair value and cost approach in accordance with the concept of accretion to the measurement of biological assets contained in PSAK 69. PSAK 69 which refers to IAS 41 emphasizes that biological assets are measured fairly and if the difference included in profit or loss in the financial statements. However, in the context of the application of commodity agribusiness in Indonesia, discrepancies are still found, therefore more studies are needed to discuss the application of PSAK 69 to agricultural commodities in Indonesia, especially in sheep farming. The focus of the research was carried out at the Kendal Open Prison Farm. The research method is a qualitative descriptive research by obtaining data through interviews and observation at the research location. The results are the recognition of the biological assets of sheep using the fair value approach is less relevant than the cost approach in agribusiness commodities in Indonesia during the transformation of the development of biological assets.